Mediterranean Sea shelters for the gold coral Savalia savaglia (Bertoloni, 1819): An assessment of potential distribution of a rare parasitic species. (July 2022) - Pulido Mantas, Torcuato; Varotti, Cecilia; Roveta, Camilla; Palma, Marco; Innocenti, Carlo; Giusti, Michela; Benabdi, Mouloud; Trainito, Egidio; Mačić, Vesna; Gambi, Maria Cristina; Cerrano, Carlo
Abstract: Savalia savaglia is an ecosystem engineer listed as Near-Threatened by the IUCN, even though effective management and proper monitoring efforts to assess its distribution is still lacking. The record of large, long-established colonies can indicate the occurrence of areas with limited human local pressure. These areas may be considered as proxies for the creation of baselines of reference useful to design restoration strategies. The aim of this work was to update the distribution of S. savaglia Mediterranean populations to develop an Ecological Niche Model, highlighting potential areas for future monitoring programs. Occurrence data were collected and harmonized into a single dataset using the scientific literature and validated observations to feed a presence-only MaxEnt model, obtaining a basin-level potential distribution of the species. The results of our study can support decision-makers in marine spatial planning measures including the preservation of mesophotic environments and prioritizing areas for conservation. Highlights: Savalia savaglia's distribution was updated for the Mediterranean region. Potential habitat of Savalia was estimated based on a presence-only MaxEnt model. Only 6.74% of the estimated suitable areas are under protection measures. Savalia' suitable areas were highlighted to implement targeted conservation measures.